IN VITRO STUDY OF CONCENTRATION-EFFECT AND TIME-COURSE PATTERN OF WHITE ALUM ON ESCHERICHIA COLI O157:H7 GROWTH - Shahriari, Reza; Salari, Saeed; Shahriari, Saeed (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Nowadays, the demand for antibacterial fabrics has increased. White alum is used for oral aphthous ulcers treatment in traditional medicine of Sistan city, Sistan and Baluchistan Province, Iran, and also as a flocculent for water purification. This study is aimed to evaluate the effect of concentration and time on antibacterial activity of white alum on Escherichia coli O157:H7. Materials and Methods: 0.25, 0.5, 1 and 2% concentrations of white alum were added to 108 CFU of Escherichia coli O157:H7. Optical Density was recorded for 4 hours. Data obtained were analyzed using Repeated Measure and Oneway ANOVA by SPSS. Results: Results revealed the effectiveness of white alum in the growth of the tested bacterium. The white alum was found to be potent against Escherichia coli O157:H7 at a concentration above 1% (p<0.05). Also, its effect is dose and time dependent, as well as other disinfectants. Conclusion: A wide variety of natural products has been under scrutiny for their clinical potential, both in terms of prevention and treatment. Strong antibacterial activity of white alum compared with control was shown against tested bacterium. In conclusion, white alum can be used as an inhibitor of bacterial growth, especially for Escherichia coli O157:H7.